Preparation method of performance-adjustable carbon-ceramic brake disc
By preparing the interface layer on the carbon fiber prefabricated body and introducing ceramic raw materials and carbon sources, and using digital-mode processing and reaction permeability technology to prepare carbon ceramic brake discs, the existing carbon ceramic brake discs are solved, and the problems of low mechanical properties, poor toughness, uneven structure and unstable performance are achieved, and a high-performance and short preparation cycle carbon ceramic brake discs are achieved.
Patent Information
- Application Number
- CN202411943158.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing carbon ceramic brake discs have problems such as low mechanical properties, poor toughness, uneven tissue, unstable performance, long preparation period and large residual Si amount.
The interface layer is prepared on the carbon fiber prefabricated body by using the reaction precursor, ceramic raw materials and carbon sources are introduced, and carbon brake discs with high density are prepared through digital-mode processing and reaction permeability processes.
By controlling the introduction of the interface layer and ceramic powder, the protection effect of carbon fiber is improved, the mechanical properties and oxidation resistance of the carbon ceramic brake disc are enhanced, the preparation cycle is shortened, and the residual Si amount is reduced.
Smart Images

Figure CN119775039A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a brake disc, and in particular to a method for preparing a carbon-ceramic brake disc with adjustable performance. Background Art
[0002] Carbon ceramic brake material is a composite material with a special structure. In recent years, carbon ceramic brake discs made of carbon ceramic brake material have been gradually used in aircraft, high-speed rail, automobiles and other fields. Carbon ceramic brake material includes: carbon fiber preform interface layer, dispersed ceramic powder, continuous carbon matrix and ceramic phase obtained by reaction.
[0003] When carbon fiber is directly combined with a ceramic matrix, a serious chemical reaction will occur, making it difficult to obtain an ideal carbon fiber preform interface layer. In order to enable carbon fiber to play a reinforcing and toughening effect, a third phase is usually introduced between the two as an interface layer to achieve a better combination of carbon fiber and ceramic matrix. Therefore, the structural design, material selection and preparation method of the interface layer will directly affect the combination of carbon fiber and ceramic matrix, and thus affect the performance of the composite material.
[0004] When carbon-ceramic brake discs are used in aircraft, high-speed rail, automobiles and other fields, they often need to undergo high-speed continuous braking, which causes the temperature of the disc surface to rise rapidly. This puts more stringent requirements on the high-temperature oxidation resistance and friction and wear performance of carbon-ceramic brake discs; traditional carbon-ceramic brake discs will oxidize and wear a lot after experiencing high temperatures for a long time. High-temperature ceramic powders are a type of material used specifically in ultra-high temperature environments, usually referring to carbides, nitrides and borides of transition metals. They have the advantages of high melting point, high thermal conductivity, moderate thermal expansion coefficient and excellent high-temperature oxidation resistance and ablation performance. Introducing high-temperature ceramic powders into carbon-ceramic brake materials can protect carbon fibers and improve the high-temperature oxidation resistance of carbon-ceramic brake materials. At the same time, due to the high density of high-temperature ceramic powders, the introduction of ceramic powders can achieve a rapid densification effect.
[0005] The carbon fiber preform needs to obtain the carbon matrix through different processes. During the preparation of the carbon matrix, it is necessary to reasonably select the carbon source and the appropriate preparation process to obtain a carbon matrix with uniform structure and high degree of graphitization, laying a good foundation for subsequent ceramicization.
[0006] The reactive melt infiltration process has the characteristics of short cycle, low cost and net size forming. This process is an industrial production technology with market competitiveness. Its core is to use molten Si to infiltrate into C / C porous body to make Si and C react chemically to generate SiC. However, it will inevitably cause damage to carbon fiber, reduce the toughening effect of carbon fiber, and lead to reduced mechanical properties, poor toughness, uneven organization, unstable performance of composite materials, long preparation cycle and high amount of residual Si. Summary of the invention
[0007] The purpose of the present invention is to solve the technical problems of existing carbon-ceramic brake discs, such as low mechanical properties, poor toughness, uneven structure, unstable performance, long preparation cycle and large amount of residual Si, and to provide a method for preparing a carbon-ceramic brake disc with adjustable performance.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] A method for preparing a carbon-ceramic brake disc with adjustable performance comprises the following steps:
[0010] 1] Using a reaction precursor to prepare an interface layer on a carbon fiber preform to obtain a carbon fiber preform with an interface layer;
[0011] 2] Introduce ceramic raw materials into the carbon fiber preform with the interface layer to obtain a density of 0.7 to 1.0 g / cm 3 A carbon fiber preform containing a ceramic component;
[0012] 3] Introducing a carbon source into a carbon fiber preform containing a ceramic component to obtain a carbon-carbon body;
[0013] 4] Processing the carbon-carbon blank according to the digital model to obtain a carbon-carbon brake disc;
[0014] 5] Use raw materials to react and infiltrate carbon-carbon brake discs to obtain a density of 1.8-2.5g / cm 3 Carbon ceramic brake disc; the particle size of the raw material ranges from 1 to 100 μm, and the amount used is 1 to 3 times that of the carbon-carbon brake disc.
[0015] Further, step 1] is specifically as follows:
[0016] Using propylene as a reaction precursor, a PyC interface layer with a thickness of 300 to 2000 nm is prepared on a carbon fiber preform to obtain a carbon fiber preform with an interface layer;
[0017] Alternatively, using BF3-NH3 or BCl3-NH3 as a reaction precursor, a BN interface layer with a thickness of 300 to 2000 nm is prepared on a carbon fiber preform by a CVI process to obtain a carbon fiber preform with an interface layer.
[0018] Further, step 2] is specifically as follows:
[0019] 2.1. Add ceramic raw materials into the container, wherein the ceramic raw materials are ceramic powder, dispersant and solvent; the particle size of the ceramic powder is in the range of 0.5 to 20 μm, and the mass thereof is 5 to 20% of the total mass; the dispersant is polyethyleneimine or sodium dodecylbenzene sulfonate, and the mass thereof is 1 to 5% of the total mass; the solvent is ethanol or water, and the mass thereof is 75 to 94% of the total mass;
[0020] 2.2. Use a rotor to stir the ceramic raw materials evenly; the speed of the rotor is 300-700 r / min;
[0021] 2.3. Introduce ceramic raw materials into the carbon fiber preform with the interface layer by ultrasonic impregnation method, vacuum impregnation method or filtration method to obtain a carbon fiber preform containing ceramic components, the density of which is 0.7-1.0 g / cm 3 .
[0022] Further, step 3] is specifically as follows:
[0023] A carbon source is introduced into a high-temperature deposition furnace at a deposition temperature of 700 to 1200°C. The carbon source is decomposed and polycondensed into carbon by high-temperature decomposition, and then introduced into the pores of a carbon fiber preform containing a ceramic component to densify the carbon fiber preform containing a ceramic component to obtain a density of 1.2 to 1.5 g / cm 3 The carbon source is natural gas or methane;
[0024] Alternatively, resin is used as a carbon source, ethanol or water is used as a solvent, a resin slurry is prepared, and a carbon fiber preform containing a ceramic component is impregnated, cured, and cracked in the resin slurry by ultrasonic impregnation, vacuum impregnation, or filtration to obtain a carbon fiber preform with a density of 1.2 to 1.5 g / cm 3 The ratio of the resin to the solvent is (20-50): (50-80).
[0025] Further, step 5] is specifically as follows:
[0026] The raw material with a particle size range of 1 to 100 μm and a dosage of 1 to 3 times that of the carbon-carbon brake disc is spread in a crucible, and then the carbon-carbon brake disc is placed on the raw material. After the top of the crucible is covered with graphite paper, the crucible is placed in a high-temperature furnace at a temperature of 1400 to 1800 ° C for 1 to 4 hours. After the high-temperature furnace is cooled to room temperature, it is taken out and finely processed to obtain a density of 1.8 to 2.5 g / cm 3 Carbon-ceramic brake discs.
[0027] Furthermore, in step 2.1, the ceramic powder is any one or more combinations of SiC powder, ZrC powder, BC powder, and WC powder.
[0028] Furthermore, in step 3], the resin is a phenolic resin or an epoxy resin; and the solvent is ethanol or water.
[0029] Furthermore, in step 5], the raw material is silicon powder or ferrosilicon alloy.
[0030] Beneficial effects of the present invention:
[0031] 1. The method for preparing a carbon-ceramic brake disc with adjustable performance of the present invention protects the carbon fiber from being oxidized at high temperature and corroded by high-temperature silicon by adding an interface layer on the carbon fiber preform and controlling the type and thickness of the interface layer, so as to obtain good mechanical properties and improve the bending strength and fracture toughness of the carbon-ceramic brake disc.
[0032] 2. The method for preparing a carbon-ceramic brake disc with adjustable performance of the present invention, the introduction of ceramic powder and the oxidation under certain oxidizing atmosphere conditions (i.e., the temperature of the carbon-ceramic brake disc will rise sharply during high-speed continuous braking, and the carbon-ceramic brake disc is exposed to the air in the service environment, which is prone to oxidation reaction. At this time, part of the ceramic powder introduced into the carbon-ceramic brake disc will undergo oxidation reaction to produce oxides to protect the carbon-ceramic brake disc) The oxidation products formed can effectively protect the matrix, ensure the antioxidant properties of the carbon-ceramic brake disc, and improve the wear resistance of the carbon-ceramic brake disc. In addition, by utilizing the high density of the added ceramic powder, the densification cycle is shortened and rapid densification is achieved; on the other hand, the internal pores of the low-density carbon fiber preform are mostly macroscopic pores, and the addition of ceramic powder can play a role in separating the pores, and a microstructure suitable for subsequent shortening of the densification cycle and siliconization is designed.
[0033] 3. The method for preparing a carbon-ceramic brake disc with adjustable performance of the present invention can reduce damage to carbon fibers by controlling the carbon source and introduction method of the carbon matrix, and can obtain a carbon matrix with uniform structure, which is helpful for the subsequent RMI (reactive melt infiltration) method.
[0034] 4. The method for preparing a carbon-ceramic brake disc with adjustable performance of the present invention controls the particle size and amount of ceramic powder and adopts a controlled reaction melt infiltration method to prepare the carbon-ceramic brake disc, so that a carbon-ceramic brake disc with uniform structure, low residual Si content and stable friction performance can be quickly prepared.
[0035] 5. The present invention provides a method for preparing a carbon-ceramic brake disc with adjustable performance. The material system of the carbon-ceramic brake disc is improved by introducing a carbon fiber preform interface layer, introducing ceramic powder, preparing a carbon matrix, and reacting to obtain a ceramic phase to obtain a carbon-ceramic brake disc with excellent performance and a short preparation cycle, thereby solving the problems of uneven structure, unstable performance, long preparation cycle, and high residual Si content of the current carbon-ceramic brake disc.
[0036] 6. The method for preparing a carbon-ceramic brake disc with adjustable performance of the present invention is optimized to solve the problem that the current carbon-ceramic brake disc has a single component, mainly composed of a carbon phase and a ceramic phase, and a single microstructure, which is carbon fiber + carbon phase + ceramic phase from the inside to the outside. The method adopts the preparation of the interface layer of the carbon fiber preform, the introduction of ceramic powder, the continuous preparation of the carbon matrix and the control of the ceramic phase obtained by the reaction. On the one hand, it enriches the matrix components of the carbon-ceramic brake disc, and on the other hand, it improves the microstructure of the carbon-ceramic brake disc, increases the control of the friction coefficient of the carbon-ceramic brake disc, and enriches the product types. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of a PyC interface layer prepared on a carbon fiber preform in step 1] of Example 1 of the method for preparing a carbon-ceramic brake disc with adjustable performance of the present invention;
[0038] Figure 2 Schematic diagram of obtaining a carbon matrix in step 3] of Example 1 of the method for preparing a carbon-ceramic brake disc with adjustable performance of the present invention;
[0039] Figure 3 A schematic diagram of the microscopic morphology of a carbon-ceramic brake disc is obtained in step 5] of Example 1 of the method for preparing a carbon-ceramic brake disc with adjustable performance of the present invention. DETAILED DESCRIPTION
[0040] Example 1
[0041] The method for preparing a carbon-ceramic brake disc with adjustable performance of the present invention comprises the following steps:
[0042] 1] Using propylene as a carbon reaction precursor, a carbon fiber preform is deposited in a high temperature deposition furnace at 1200°C for 30 hours to prepare a PyC interface layer, and a carbon fiber preform with a PyC interface layer thickness of 300-400nm is obtained; Figure 1 As shown, the thicknesses of the two PyC interface layers are 366nm and 374nm respectively.
[0043] 2] Add ceramic raw materials into the container. The ceramic raw materials are ceramic powder, dispersant and solvent. The ceramic powder is SiC powder with a particle size of 20 μm and a mass of 20% of the total mass. The dispersant is polyethyleneimine with a mass of 5% of the total mass. The solvent is water with a mass of 75% of the total mass. The ceramic raw materials are stirred evenly by a rotor. The rotor speed is 700 r / min. The ceramic raw materials are introduced into the carbon fiber preform with an interface layer by ultrasonic impregnation to obtain a density of 1.0 g / cm 3 A carbon fiber preform containing a ceramic component;
[0044] 3] Phenolic resin is used as a carbon source and ethanol is used as a solvent to prepare a resin slurry, wherein the ratio of phenolic resin to ethanol is 50:50, to obtain a resin slurry; a carbon fiber preform containing a ceramic component is impregnated in the resin slurry by a vacuum impregnation method, and then cured in an oven and pyrolyzed at 1000°C to obtain a density of 1.5 g / cm 3 Carbon-carbon blanks, such as Figure 2 As shown, the ceramic powder and carbon matrix in the carbon-carbon body are evenly distributed in the gaps between the carbon fibers;
[0045] 4] Processing the carbon-carbon blank according to the digital model to obtain a carbon-carbon brake disc;
[0046] 5] Si powder with a particle size of 100 μm and a dosage of 3 times that of the carbon-carbon brake disc was spread in a crucible, and then the carbon-carbon brake disc was placed on the raw material. After covering the top of the crucible with graphite paper, the crucible was placed in a high-temperature furnace at a temperature of 1800°C for 4 hours. After cooling to room temperature, it was taken out and finely processed to obtain a density of 2.5 g / cm 3 Carbon-ceramic brake discs;
[0047] like Figure 3 As shown, the appearance and structure of the carbon ceramic brake disc obtained after reaction dissolution is uniform, and the carbon fiber is protected by the PyC interface layer and is not corroded. The bending strength of the carbon ceramic brake disc was tested at 5 locations, as shown in Table 1:
[0048] Sample block 1 Sample block 2 Sample block 3 Sample block 4 Sample block 5 average value 251.61 218.65 188.44 179.9 252.81 218.29
[0049] Among them, the average bending strength is 218.29MPa, and the mechanical properties are good.
[0050] The present invention obtains a carbon fiber preform with an interface layer having better mechanical properties by controlling the type and thickness of the interface layer; and prepares a carbon-ceramic brake disc by controlling the particle size and amount of the raw materials and adopting a controlled reaction melt infiltration method, so as to quickly prepare a carbon-ceramic brake disc with uniform structure, less residual Si content and stable friction performance.
[0051] Example 2
[0052] 1] Using propylene as a carbon reaction precursor, a carbon fiber preform was deposited in a high temperature deposition furnace at 700°C for 120 hours to prepare a PyC interface layer, and a carbon fiber preform with a PyC interface layer thickness of 1700-2000nm was obtained;
[0053] 2] Add ceramic raw materials into the container. The ceramic raw materials are ceramic powder, dispersant and solvent. The ceramic powder is ZrC powder with a particle size of 0.5 μm and a mass of 5% of the total mass. The dispersant is polyethyleneimine with a mass of 1% of the total mass. The solvent is ethanol with a mass of 94% of the total mass. The ceramic raw materials are stirred evenly by a rotor. The speed of the rotor is 300 r / min. The ceramic raw materials are introduced into the carbon fiber preform with an interface layer by ultrasonic impregnation to obtain a density of 0.7 g / cm 3 A carbon fiber preform containing a ceramic component;
[0054] 3] Using methane as the carbon source, a carbon matrix was deposited in a high-temperature deposition furnace at a deposition temperature of 700°C. The carbon source was decomposed and polycondensed into carbon through high-temperature decomposition, and then introduced into the pores of the carbon fiber preform containing the ceramic component to densify the carbon fiber preform containing the ceramic component to obtain a density of 1.2 g / cm 3 Carbon-carbon body;
[0055] 4] Processing the carbon-carbon blank according to the digital model to obtain a carbon-carbon brake disc;
[0056] 5] Place ferrosilicon alloy with a particle size of 50 μm and a dosage of 3 times that of the carbon-carbon brake disc in a crucible, then place the carbon-carbon brake disc on the raw material, cover the top of the crucible with graphite paper, and place the crucible in a high-temperature furnace at 1800°C for 1 hour. After cooling to room temperature, take it out and perform fine processing to obtain a density of 1.8 g / cm 3 Carbon-ceramic brake discs.
[0057] The present invention adopts the above-mentioned method and raw materials to control the interface layer of the carbon fiber preform, the introduction of ceramic powder, the preparation of the carbon matrix and the generation of the reaction ceramic phase, and quickly prepares a carbon-ceramic brake disc with uniform structure, good mechanical properties, stable friction performance and good antioxidant performance.
[0058] Example 3
[0059] 1] Using BF3-NH3 as a reaction precursor, the carbon fiber preform was deposited in a high temperature deposition furnace at 1200°C for 30 hours to prepare a PyC interface layer, and a carbon fiber preform with a PyC interface layer thickness of 600-700nm was obtained;
[0060] 2] Add ceramic raw materials into the container. The ceramic raw materials are ceramic powder, dispersant and solvent. The ceramic powder is BC powder and WC powder (ratio is 1:1), the particle size is 10μm, and the mass is 15% of the total mass; the dispersant is sodium dodecylbenzene sulfonate, the mass is 4% of the total mass; the solvent is water, the mass is 80% of the total mass; the ceramic raw materials are stirred evenly by a rotor; the rotor speed is 600r / min; the carbon fiber preform with the interface layer is introduced into the ceramic raw materials by suction filtration to obtain a density of 0.9g / cm 3 A carbon fiber preform containing a ceramic component;
[0061] 3] Use epoxy resin as carbon source and ethanol as solvent to prepare resin slurry, wherein the ratio of phenolic resin to ethanol is 40:60, to obtain resin slurry; use suction filtration method to impregnate the carbon fiber preform containing ceramic component in the resin slurry, and then cure it in an oven and pyrolyze it at 900℃ to obtain a density of 1.2g / cm 3 Carbon-carbon body;
[0062] 4] Processing the carbon-carbon blank according to the digital model to obtain a carbon-carbon brake disc;
[0063] 5] Si powder with a particle size of 5 μm and twice the amount of carbon-carbon brake disc was spread in a crucible, and then the carbon-carbon brake disc was placed on the raw material. After covering the top of the crucible with graphite paper, the crucible was placed in a high-temperature furnace at a temperature of 1600°C for 2 hours. After cooling to room temperature, it was taken out and finely processed to obtain a density of 2.0 g / cm 3 Carbon-ceramic brake discs.
[0064] Example 4
[0065] 1] Using BCl3-NH3 as a reaction precursor, the carbon fiber preform was deposited in a high temperature deposition furnace at 1200°C for 30 hours to prepare a PyC interface layer, and a carbon fiber preform with a PyC interface layer thickness of 800-900nm was obtained;
[0066] 2] Add ceramic raw materials into the container. The ceramic raw materials are ceramic powder, dispersant and solvent. The ceramic powder is WC powder with a particle size of 1 μm and a mass of 16% of the total mass. The dispersant is sodium dodecylbenzene sulfonate with a mass of 3% of the total mass. The solvent is water with a mass of 81% of the total mass. Use a rotor to stir the ceramic raw materials evenly. The rotor speed is 500 r / min. Use a vacuum impregnation method to introduce the ceramic raw materials into the carbon fiber preform with an interface layer to obtain a density of 0.8 g / cm 3 A carbon fiber preform containing a ceramic component;
[0067] 3] Use epoxy resin as carbon source and ethanol as solvent to prepare resin slurry, wherein the ratio of phenolic resin to ethanol is 20:80, to obtain resin slurry; use suction filtration method to impregnate the carbon fiber preform containing ceramic component in the resin slurry, and then cure it in an oven and pyrolyze it at 1100℃ to obtain a density of 1.3g / cm 3 Carbon-carbon body;
[0068] 4] Processing the carbon-carbon blank according to the digital model to obtain a carbon-carbon brake disc;
[0069] 5] Si powder with a particle size of 4 μm and a dosage of 1 times that of the carbon-carbon brake disc was spread in a crucible, and then the carbon-carbon brake disc was placed on the raw material. After covering the top of the crucible with graphite paper, the crucible was placed in a high-temperature furnace at a temperature of 1500°C for 3 hours. After cooling to room temperature, it was taken out and finely processed to obtain a density of 2.1 g / cm 3 Carbon-ceramic brake discs.
[0070] Example 5
[0071] 1] Using BF3-NH3 as a reaction precursor, the carbon fiber preform was deposited in a high temperature deposition furnace at 1200°C for 30 hours to prepare a PyC interface layer, and a carbon fiber preform with a PyC interface layer thickness between 1000-1600nm was obtained;
[0072] 2] Add ceramic raw materials into the container. The ceramic raw materials are ceramic powder, dispersant and solvent. The ceramic powder is BC powder with a particle size of 0.8 μm and a mass of 18% of the total mass. The dispersant is sodium dodecylbenzene sulfonate with a mass of 2% of the total mass. The solvent is water with a mass of 80% of the total mass. Use a rotor to stir the ceramic raw materials evenly. The rotor speed is 400 r / min. Use a suction filtration method to introduce the ceramic raw materials into the carbon fiber preform with an interface layer to obtain a density of 0.9 g / cm 3 A carbon fiber preform containing a ceramic component;
[0073] 3] Using natural gas as the carbon source, a carbon matrix was deposited in a high-temperature deposition furnace at a deposition temperature of 1200°C. After the carbon source was decomposed and polycondensed into carbon by high-temperature decomposition, it was introduced into the pores of the carbon fiber preform containing the ceramic component to densify the carbon fiber preform containing the ceramic component to obtain a density of 1.4 g / cm 3 Carbon-carbon body;
[0074] 4] Processing the carbon-carbon blank according to the digital model to obtain a carbon-carbon brake disc;
[0075] 5] Si powder with a particle size of 1 μm and an amount 1.5 times that of the carbon-carbon brake disc was spread in a crucible, and then the carbon-carbon brake disc was placed on the raw material. After covering the top of the crucible with graphite paper, the crucible was placed in a high-temperature furnace at a temperature of 1550°C for 2 hours. After cooling to room temperature, it was taken out and finely processed to obtain a density of 2.0 g / cm 3 Carbon-ceramic brake discs.
Claims
1. A method for preparing a carbon-ceramic brake disc with adjustable performance, characterized in that: The following steps are involved: 1] Using a reaction precursor to prepare an interface layer on a carbon fiber preform to obtain a carbon fiber preform with an interface layer; 2] Introduce ceramic raw materials into the carbon fiber preform with the interface layer to obtain a density of 0.7 to 1.0 g / cm 3 A carbon fiber preform containing a ceramic component; 3] Introducing a carbon source into a carbon fiber preform containing a ceramic component to obtain a carbon-carbon body; 4] Processing the carbon-carbon blank according to the digital model to obtain a carbon-carbon brake disc; 5] Use raw materials to react and infiltrate carbon-carbon brake discs to obtain a density of 1.8-2.5g / cm 3 Carbon ceramic brake disc; the particle size of the raw material ranges from 1 to 100 μm, and the amount used is 1 to 3 times that of the carbon-carbon brake disc.
2. The method for preparing a carbon-ceramic brake disc with adjustable performance according to claim 1, characterized in that: Step 1] Specifically: Using propylene as a reaction precursor, a PyC interface layer with a thickness of 300 to 2000 nm is prepared on a carbon fiber preform to obtain a carbon fiber preform with an interface layer; Alternatively, using BF3-NH3 or BCl3-NH3 as a reaction precursor, a BN interface layer with a thickness of 300 to 2000 nm is prepared on a carbon fiber preform by a CVI process to obtain a carbon fiber preform with an interface layer.
3. The method for preparing a carbon-ceramic brake disc with adjustable performance according to claim 2, characterized in that: Step 2] Specifically: 2.
1. Add ceramic raw materials into the container, wherein the ceramic raw materials are ceramic powder, dispersant and solvent; the particle size of the ceramic powder is in the range of 0.5 to 20 μm, and the mass thereof is 5 to 20% of the total mass; the dispersant is polyethyleneimine or sodium dodecylbenzene sulfonate, and the mass thereof is 1 to 5% of the total mass; the solvent is ethanol or water, and the mass thereof is 75 to 94% of the total mass; 2.
2. Use a rotor to stir the ceramic raw materials evenly; the speed of the rotor is 300-700 r / min; 2.
3. Introduce ceramic raw materials into the carbon fiber preform with the interface layer by ultrasonic impregnation method, vacuum impregnation method or filtration method to obtain a carbon fiber preform containing ceramic components, the density of which is 0.7-1.0 g / cm 3 .
4. The method for preparing a carbon-ceramic brake disc with adjustable performance according to claim 3, characterized in that: Step 3] Specifically: A carbon source is introduced into a high-temperature deposition furnace at a deposition temperature of 700 to 1200°C. The carbon source is decomposed and polycondensed into carbon by high-temperature decomposition, and then introduced into the pores of a carbon fiber preform containing a ceramic component to densify the carbon fiber preform containing a ceramic component to obtain a density of 1.2 to 1.5 g / cm 3 The carbon source is natural gas or methane; Alternatively, resin is used as a carbon source, ethanol or water is used as a solvent, a resin slurry is prepared, and a carbon fiber preform containing a ceramic component is impregnated, cured, and cracked in the resin slurry by ultrasonic impregnation, vacuum impregnation, or filtration to obtain a carbon fiber preform with a density of 1.2 to 1.5 g / cm 3 The ratio of the resin to the solvent is (20-50): (50-80).
5. The method for preparing a carbon-ceramic brake disc with adjustable performance according to claim 4, characterized in that: Step 5] Specifically: The raw material with a particle size range of 1 to 100 μm and a dosage of 1 to 3 times that of the carbon-carbon brake disc is spread in a crucible, and then the carbon-carbon brake disc is placed on the raw material. After the top of the crucible is covered with graphite paper, the crucible is placed in a high-temperature furnace at a temperature of 1400 to 1800 ° C for 1 to 4 hours. After the high-temperature furnace is cooled to room temperature, it is taken out and finely processed to obtain a density of 1.8 to 2.5 g / cm 3 Carbon-ceramic brake discs.
6. The method for preparing a carbon-ceramic brake disc with adjustable performance according to claim 3, characterized in that: In step 2.1, the ceramic powder is any one or a combination of SiC powder, ZrC powder, BC powder, and WC powder.
7. The method for preparing a carbon-ceramic brake disc with adjustable performance according to claim 4, characterized in that: In step 3], the resin is phenolic resin or epoxy resin; and the solvent is ethanol or water.
8. The method for preparing a carbon-ceramic brake disc with adjustable performance according to claim 6, characterized in that: In step 5], the raw material is silicon powder or ferrosilicon alloy.
Citation Information
Patent Citations
Preparation method of carbon-ceramic brake disc
CN111892416A
Preparation method of carbon / ceramic composite material
CN116143535A
Preparation method of carbon-ceramic composite material
CN117776759A
High-thermal-conductivity low-expansion carbon ceramic material and preparation method thereof
CN117923931A
Method for preparing carbon-ceramic brake material and method for preparing carbon-ceramic brake disc
WO2017107735A1
Cited By
Silicon-chromium alloy synergistically modified carbon / ceramic brake disc and preparation method thereof
CN121470979A
A silicon-chromium alloy synergistically modified carbon / ceramic brake disc and a preparation method thereof
CN121470979B